2018
DOI: 10.1186/s13018-018-0841-y
|View full text |Cite
|
Sign up to set email alerts
|

Squeaking in fourth-generation ceramic-on-ceramic total hip replacement and the relationship with prosthesis brands: meta-analysis and systematic review

Abstract: BackgroundPostoperative squeaking in patients who applied the fourth-generation ceramic bearing in primary hip replacement has not been reported systematically; we aim to study the squeaking incidence in the fourth-generation ceramic bearing and related risk factors for squeaking, and we also attempt to explore the relationship between squeaking and prosthetic brands.MethodsThe PubMed, Embase, and Cochrane library were searched, and 14 articles were finally included. Patients’ demographic data, surgical-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 49 publications
1
8
1
8
Order By: Relevance
“…The percentage of patients who reported squeaking was 12%, which is within the range available from previous studies [6,41,53]. In the future, multicenter studies with large sample sizes or studies based on national databases may be able to further confirm our findings.…”
Section: Percentage Of Patients Reporting Squeakingsupporting
confidence: 87%
See 1 more Smart Citation
“…The percentage of patients who reported squeaking was 12%, which is within the range available from previous studies [6,41,53]. In the future, multicenter studies with large sample sizes or studies based on national databases may be able to further confirm our findings.…”
Section: Percentage Of Patients Reporting Squeakingsupporting
confidence: 87%
“…Some studies have shown that specific implants may be more likely to be associated with squeaking, possibly because of their anatomic design [15,40,44,53]. Because of the availability of prostheses for the index surgery, we mixed and matched implants from different manufacturers (combination of the Corail stem and Betacup).…”
Section: Characteristics Of Squeaking and Association Between Squeaki...mentioning
confidence: 99%
“…Squeaking or clicking is another complication, though not specific for CoC articulation, but more common and sometimes more audible when compared with metal-on-polyethylene articulations. Zhao et al 49 performed a systematic review of 14 articles that evaluated occurrence of squeaking in fourth-generation CoC THAs. They arrived at an overall incidence of 3%, with remarkable variations depending on implant design.…”
Section: Articulating Materialsmentioning
confidence: 99%
“…Stanat and Capozzi24 conducted a meta-analysis on the third-generation CoC THAs and yielded a squeaking incidence of 2.4%. Zhao et al25…”
mentioning
confidence: 99%